The Use of Swear Words in The Corpus of Contemporary American English (COCA): Sociolinguistics Study - Ten, Angela; CM Simatupang, Ervina (International Journal of Psychosocial Rehabilitation, 2020)
The title of this study is The Use of Swear Words in the Corpus of Contemporary American English (COCA): Sociolinguistics Study. The aim of this study is to analyse and scrutinize the frequently used swear words in the Corpus of Contemporary American English (COCA) in view of their themes and functions. The method used in carrying out the study is the descriptive analysis method. The source of data used is taken from the official website of the Corpus of Contemporary American English (COCA). The result of the research demonstrates that there are four frequently used swear words in the Corpus of Contemporary American English (COCA). They are motherfucker with 770 occurrences (2%), asshole with 2386 occurrences (5%), fuck with 11098 occurrences (22%), shit with 17008 occurrences (34%), and damn with 18407 occurrences. There are four themes of swear words found: the religious theme, the scatological theme, the sexual activity theme, and the mother (family) theme. All four themes are represented with the same amount of data. There are four functions of swear words found. They are stand-alone functions: (1) expletive interjections (28%), (2) name-calling (29%), and slot filler functions: (3) emphasis (29%), (4) adverbial/adjectival intensifier (14%).